2022
DOI: 10.1057/s41264-022-00165-w
|View full text |Cite
|
Sign up to set email alerts
|

The potential of crowdfunding to promote business in the context of an emerging economy

Abstract: Crowdfunding has the potential to change the historic standards of the financial services industry and reduce gaps between supply and demand economics. Over the past ten years, it has received increasing attention. However, the potential that crowdfunding holds in less fortunate economic contexts where SMEs are probably needed the most has not yet attracted the attention that it deserves. Acknowledging the influence of knowledge about crowdfunding, this research explores the viability of crowdfunding as a sour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Crowdfunding success rates have boosted the growth of SMEs in developed countries, but developing countries have not sufficiently benefited from it (Edem, et al, 2021). Another study by Erasmus, et al, (2022) indicated that the potential which crowdfunding offers in less favorable economic conditions, where SMEs are most likely to be assisted, has yet to receive the attention it deserves. Given the willingness to finance even start-up SMEs, it shows the importance of raising awareness of crowdfunding among the general public.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Crowdfunding success rates have boosted the growth of SMEs in developed countries, but developing countries have not sufficiently benefited from it (Edem, et al, 2021). Another study by Erasmus, et al, (2022) indicated that the potential which crowdfunding offers in less favorable economic conditions, where SMEs are most likely to be assisted, has yet to receive the attention it deserves. Given the willingness to finance even start-up SMEs, it shows the importance of raising awareness of crowdfunding among the general public.…”
Section: Discussionmentioning
confidence: 99%
“…Given the willingness to finance even start-up SMEs, it shows the importance of raising awareness of crowdfunding among the general public. Erasmus, et al, (2022) also suggest that the motivation for entrepreneurs to participate in crowdfunding is not necessarily financial-driven. Realizing the potential of crowdfunding in assisting the SMEs as mentioned above, the factors for SMEs to use crowdfunding are yet to be further discovered in this study.…”
Section: Discussionmentioning
confidence: 99%